Selenium supplementation and pregnancy outcomes - Dahlen, Carl R.; Reynolds, Lawrence P.; Caton, Joel S. (Frontiers in Nutrition, 2022)
In vertebrates and invertebrates, selenium (Se) deficiency or excess is associated with gonadal insufficiency and gamete dysfunction in both males and females, leading to implantation failure, altered embryonic development and, ultimately, infertility. During pregnancy, Se excess or deficiency is associated with miscarriage, pre-eclampsia (hypertension of pregnancy), gestational diabetes, fetal growth restriction and preterm birth. None of this is surprising, as Se is present in high concentrations in the ovary and testes, and work in animal models has shown that addition of Se to culture media improves embryo development and survival in vitro in association with reduced reactive oxygen species and less DNA damage. Selenium has also been shown to affect uterine function and conceptus growth and gene expression. Similarly, Se improves testicular function including sperm count, morphology and motility, and fertility. Using animal models, supplementation of Se in the maternal diet during early pregnancy has been shown to improve substrate supply and utilization of the fetus and to alter fetal body and organ growth. Supplementation of Se throughout pregnancy affected maternal whole-body and organ growth and vascular development, and also affected expression of angiogenic factors in maternal and fetal organs. Supplemental Se throughout pregnancy also affected placental growth, which may explain in part its effects on fetal growth and development, and also affected mammary gland development, colostrum yield and composition as well as postnatal development of the offspring. In conclusion, Se supplementation during pregnancy can potentially improve fertility and pregnancy outcomes, and thereby improve postnatal growth and development. Expanded research efforts therefore warranted to examine in more detail and more species the potential benefits of Se supplementation in reproductive processes in mammals.